PHARMACEUTICAL STANDARDIZATION OF GANDHAKAKALPA - Vadipilla, *Shyamala; Rameshbabu, G (International Journal of Ayurveda and Pharma Research, 2018)
Rasa Shastra is the pharmaceutical branch of Ayurveda which deals with the processing of metals and minerals having therapeutic importance. Rasa Oushadhies are the potent Ayurvedic preparations mainly containing metals and minerals.These Oushadhies possess wide range of therapeutic efficacy and are considered superior because of their qualities like small dose, quick action, palatability and longer shelf life. Gandhakakalpa is a Rasoushadhi mentioned in Basavarajeeyam 18th chapter 20th sloka indicated for Sthoulya. Gandhaka (Sulphur) and Madhuka thaila are the main ingredients of Gandhaka kalpa. Shodhana (purification), Murchchana, Mardana (trituration) are the important steps involved in preparation of Gandhaka kalpa. Shuddha Gandhaka & Murchchita Madhuka thaila were taken. After obtaining homogenous mixture, it was made into 500mg tablets. Till now,no research work has been carried out to standardize this formulation. Therefore, the present study has been planned to standardize the method of preparation of Gandhaka kalpa according to the method explained in the classical literature.